Benchmarking the performance of heavy earthmoving machines – a review - Yadav P.K.; Gupta S.; Kumar D. (My University, 2025)
A desirable benchmark should be complete from all aspect, holistic in nature and conceptually universal as well as acceptable. This work reviews the related literature and conclude that different types of benchmarking methods are used in different organizations and institutions. The ever-increasing demand for continuous improvement of quality and performance in any field or organization leads to benchmarking. Benchmarking is an effective technique, which supports innovative ideas. The present study aims to provide an inclusive review of performance benchmarking. In this work, different types of benchmarking techniques are categorized, and their drawbacks and the research trends are provided to assist researchers and practitioners in conducting new research in this area. A new benchmarking methodology has been suggested which could be acceptable universally for all the heavy earthmoving machines (HEMMs) which provides numerical benchmarked value which can be easily used for the comparison purpose. © 2021, Books and Journals Private Ltd.. All rights reserved.